2023
DOI: 10.1177/21925682231155844
|View full text |Cite
|
Sign up to set email alerts
|

Determining Prior Authorization Approval for Lumbar Stenosis Surgery With Machine Learning

Abstract: Study Design Medical vignettes. Objectives Lumbar spinal stenosis (LSS) is a degenerative condition with a high prevalence in the elderly population, that is associated with a significant economic burden and often requires spinal surgery. Prior authorization of surgical candidates is required before patients can be covered by a health plan and must be approved by medical directors (MDs), which is often subjective and clinician specific. In this study, we hypothesized that the prediction accuracy of machine lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…De Barros et al discovered that the machine learning model had superior predictive accuracy, assessed by root mean square error, relative to recommendations made by individual medical directors, with root mean square error values of 0.1123 and 0.2661, respectively. 32 The AUROC and Cohen’s kappa for the machine learning model were 0.959 and 0.801, respectively, compared with the individual medical directors’ recommendations of 0.844 and 0.564, respectively. These results suggest that AI can be effectively applied to prior authorization approvals for lumbar spinal stenosis surgery.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…De Barros et al discovered that the machine learning model had superior predictive accuracy, assessed by root mean square error, relative to recommendations made by individual medical directors, with root mean square error values of 0.1123 and 0.2661, respectively. 32 The AUROC and Cohen’s kappa for the machine learning model were 0.959 and 0.801, respectively, compared with the individual medical directors’ recommendations of 0.844 and 0.564, respectively. These results suggest that AI can be effectively applied to prior authorization approvals for lumbar spinal stenosis surgery.…”
Section: Introductionmentioning
confidence: 93%
“…These results suggest that AI can be effectively applied to prior authorization approvals for lumbar spinal stenosis surgery. 32 Broadly, AI can be extremely valuable for billing procedures in a plastic surgery practice by way of streamlining CPT codes in billing, reducing coding errors, and assisting with prior authorization approvals. However, the incorporation of AI into billing practices can lead to competing goals for providers and payers.…”
Section: Takeawaysmentioning
confidence: 99%
See 2 more Smart Citations
“…In outcome predictions for LSS, researchers have also reported several ML studies such as patient-reported outcome measures [ 16 , 17 ], clinical outcome predictions [ 18 , 19 , 20 , 21 ], patient-specific outcomes (such as patient resource utilization [ 22 ], non-home discharge placement prediction [ 23 ], prolonged opioid prescriptions [ 24 ], and prolonged length of hospital stay [ 25 ]). Other ML studies, such as surgical candidacy prediction [ 26 ] and prior authorization approval prediction [ 27 ], have been also reported.…”
Section: Introductionmentioning
confidence: 99%